2018
DOI: 10.18060/22898
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of the Journal of Legal Aspects of Sport: 1992-2016

Abstract: As the flagship journal of the Sport and Recreation Law Association, the Journal of Legal Aspects of Sport (JLAS) serves “…as an interdisciplinary outlet for legal issues in the sport, recreation, and related fields to meet the needs of researchers, academicians, practitioners, and policymakers” (About JLAS, para. 2). A study by Batista and Pittman (2006) identified JLAS as the most highly ranked sport law journal among journals focusing on sport management. Articles appearing in the Journal of Legal Aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Content analysis has become a popular method for qualitative and quantitative analyses in management and international business research (Gaur and Kumar, 2018 ). Prior studies within the sport management field have also utilized this method (Pederson and Pitts, 2001 ; Peetz and Reams, 2011 ; Miller et al, 2018 ; Williams et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Content analysis has become a popular method for qualitative and quantitative analyses in management and international business research (Gaur and Kumar, 2018 ). Prior studies within the sport management field have also utilized this method (Pederson and Pitts, 2001 ; Peetz and Reams, 2011 ; Miller et al, 2018 ; Williams et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is a systematic and quantitative research method (Vaismoradi et al, 2013). The method has been applied to a range of equity, diversity, and inclusion issues (Rosa et al, 2016;Taylor, 2003), including issues specific to physical activity and recreation (Bruning et al, 2020;Cardinal et al, 2009Gietzen et al, 2017;Kamphoff et al, 2010;Miller et al, 2019;Thomas & Cardinal, 2020;White & Cardinal, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Gender was assumed on the basis of the first names of the authors (Wais, 2016). Because an author's gender may reflect the nature and types of research questions being asked, and female and male scholars are widely observed to publish at different rates (Miller et al, 2019), potential problems emerge, such as the one-way mirror phenomenon whereby certain voices dominate the published literature (Valentine et al, 1999;Williams et al, 2018).…”
Section: Methodsmentioning
confidence: 99%